Measure of Head Impacts in Hockey, Football, and Soccer - Richter, C. J.; Naunheim, R.; Standeven, J.; Lewis, L. M. (Academic Emergency Medicine, 2000)
Objectives: The purpose of this study was to quantify the impacts suffered by the heads of players involved in hockey, football, and soccer in G-forces. It is poorly understood what the long-term consequences of these repeated impacts are. It is hoped that this type of research can help make these sports safer for the participants. Methods: This was a prospective observational study using triaxial accelerometers to measure and graph velocity changes at the point of impact with the head. The accelerometers were placed in the vertex of a standard football and hockey helmet. The football helmet and hockey helmet were then worn by a high school player in game situations of each sport with each impact recorded ona triaxial graph by computer. The football helmet was also worn by a player in soccer practice who "headed" standard soccer balls to equilibrate the measurements across sports. The measurements were recorded by the accelerometers in G-forces and then the three sports were compared by ANOVA. Results: There were 158 football impacts, 161 hockey impacts, and 25 soccer impacts recorded. The measured forces were: an average of 29.2 ± 1.1 Gs in football, 35.0 ± 1.7 in hockey, and 54.7 ± 4.1 in soccer. These differences are statistically significant at p < 0.05. Conclusions: Using these data we concluded that the impacts suffered by the heads of players in each of these sports are impressive and that soccer players received the strongest impacts of the three sports.